Electronic Medical Records in the American Health System: challenges and lessons learned - Janett, Robert S.; Yeracaris, Peter Pano (Ciência & saude coletiva, 2020)
Abstract Electronic medical records have been touted as a solution to many of the shortcomings of health care systems. The aim of this essay is to review pertinent literature and present examples and recommendations from several decades of experience in the use of medical records in primary health care, in ways that can help primary care doctors to organize their work processes to improve patient care. Considerable problems have been noted to result from a lack of interoperability and standardization of interfaces among these systems, impairing the effective collaboration and information exchange in the care of complex patients. It is extremely important that regional and national health policies be established to assure standardization and interoperability of systems. Lack of interoperability contributes to the fragmentation of the information environment. The electronic medical record (EMR) is a disruptive technology that can revolutionize the way we care for patients. The EMR has been shown to improve quality and reliability in the delivery of healthcare services when appropriately implemented. Careful attention to the impact of the EMR on clinical workflows, in order to take full advantage of the potential of the EMR to improve patient care, is the key lesson from our experience in the deployment and use of these systems. Resumo Os registros médicos eletrônicos (RME) têm sido apontados como uma solução para muitas das deficiências dos sistemas de saúde. O objetivo deste ensaio é revisar a literatura pertinente e apresentar exemplos e recomendações de várias décadas de experiência no uso de registros médicos na atenção primária à saúde, de maneira a ajudá-los na organização de seus processos de trabalho para melhorar o atendimento ao paciente. Observou-se que problemas consideráveis resultam da falta de interoperabilidade e padronização de interfaces entre esses sistemas, prejudicando a colaboração efetiva e a troca de informações no atendimento a pacientes complexos. É extremamente importante que políticas regionais e nacionais de saúde sejam estabelecidas para garantir a padronização e interoperabilidade dos sistemas. A falta de interoperabilidade contribui para a fragmentação do ambiente de informações. O prontuário eletrônico (RME) é uma tecnologia disruptiva que pode revolucionar a maneira como cuidamos dos pacientes. Foi demonstrado que o RME melhora a qualidade e a confiabilidade na prestação de serviços de saúde quando implementada adequadamente. Uma atenção cuidadosa ao impacto do RME nos fluxos de trabalho clínicos, a fim de aproveitar ao máximo o potencial do RME para melhorar o atendimento ao paciente, é a principal lição de nossa experiência na implantação e uso desses sistemas.